Aplikasi Kamus Data Virus Penyakit Di Dunia Berbasis Web Menggunakan Metode Binary Search - Ferdian, Ridho; Aulia, Rahmat; Prayogi, Satria Yudha (INCODING: Journal of Informatics and Computer Science Engineering, 2022)
The low level of public knowledge cannot be separated from the lack of media and information that presents articles about various kinds of viral diseases, making young and old people neglect to maintain health because they do not follow existing health protocols and can have a negative impact on the spread of viruses that cause disease. This research focuses on designing a web-based world virus disease data dictionary application using the binary search method. The purpose of this research is to make the application easily accessible to the public, especially those who have minimal technological knowledge by applying the binary search method which is useful for making searches easier. The results of this research are in the form of application design that is carried out to the usability testing stage to produce applications that have high usability by testing the community or people who are not familiar with the technology.